Five on finniston farm - Blyton, Enid; Soper, Eileen Alice Soper, Eileen L. (Hodder Children's London, 2000)
The Famous Five hunt for the lost dungeons of a ruined castle on Finniston Farm. The friends are determined to find them, and whatever they hide, but they are not alone. Can the Famous Five get there first?